The Synergy of the Tri-Center Education in Shaping Social Responsibility Theoretical and Practical Review - Zuhdi Esha; Asep Mulyana; Uswatun Hasanah; Ummu Aiman (Jurnal Ar Ro'is Mandalika (Armada), 2026)
Education is not solely the responsibility of formal institutions, but rather a multidimensional process involving family, school, and community the three centers of education as proposed by Ki Hajar Dewantara. In this article, we develop a three-center educational framework as a basis for fostering students' social responsibility. Using a qualitative approach in the form of a literature review, this article examines the roles and responsibilities of each pillar (family, school, and community) and formulates collaborative mechanisms that enable the holistic internalization of prosocial values. Based on an analysis of recent studies, we found that the three-center educational framework is relevant and effective in strengthening character education and social responsibility, especially in the context of modern challenges such as individualism and digital disruption. Therefore, systematic synergy between these three pillars is necessary as a character education strategy in the 21st century.